The effects of exercise-induced dehydration on psychomotor and physiological variables in relaxation trained army reserved personnels during prolonged walking in the heat - Hairul Anuar, Hashim (Pusat Pengajian Sains Perubatan, 2013)
Prolonged engagement in the hot environment is common among military men and women. Inherently, it can lead to fluid losses reaching rates of 1 - 2 L per hour (Coyle, 1994), which can lead to dehydration. A number of studies have shown that dehydration could lead a drop in performance levels for various fundamental cognitive-motor abilities (Cian et al., 2000; Cian et al., 2001; Gopinathan et al., 1988; Nielsen eta/., 1990; Sharma et al., 1986) as well as physical performance (Terrados & Maughan, 1995). Although dehydration can be easily prevented by ensuring adequate fluid intake, in some circumstanes, such as an actual battle, fluid supply may not be readily available. Additional strategy to sustain mental and physical readiness in such conditions seem desirable. Relaxation has been used in numerous clinical and non clinical settings such as clinical, sports, and schools. However, to our knowledge, the effects of relaxation training on mental performance and physiological parameters in the dehydrated condition among military personnel have not been studied. Given that soldiers need to be in an optimal state of physical and mental readiness at all time, the benefits of relaxation training as a strategy to enhance their mental performance is worthy of further investigation. The aim of this study is twofold, first, we sought to examine the effects of dehydration on psychomotor and physiological variables in army reserved personel and second, to examine the effect of relaxation training in exercise-induced dehydrated army reserved personnel exercising in the heaf Twenty six reserved army male participated in this study. they were matched into hydrated and dehydrated groups based on age, V02max. body mass index, and body fat percentage. Once familiriazed with the experimenal protocols, they were required to undergo two sessions of 3-hour walking in the lab-induced hot environment (31°C). In between these two sessions, the subjects completed an eight sessions of 30-min progressive muscle relaxation training. Psychomotor performance and blood samples were collected at baseline, and after every 1 hour of walking in each session. Other parameters (heart rate, V02, ratings of perceived exertion, rectal temperature) were collected every 20 minutes i nterva I. The results revealed a significantly higher percentage of body weight loss in the dehydrated group (2.3 ± 1.2%) compared to the hydrated group (1.1 ± 0.7%). These data demonstrated that consumption of sufficient fluid during prolonged walking among reserved army personnels is advisable to avoid the potential adverse effects of dehydration. Significant differences between the two groups were also found in heart rate and creatine kinase. No significant differences were found between the two groups in other parameters. However, there are positive physiological pattern of hydrated group compared to the dehydrated group. In relation to the relaxation response to dehydration, it was observed that relaxation training significantly slowed down the increase in CK value and lowered exercising heart rate. No other parameters were significant although positive indications of the benefits of relaxation were observed (eg., lower oxygen consumption). The findings partially support the notion of that relaxation training is beneficial to moderate the negative effects of dehydration in male military reserved personnels engaging in prolonged walking in the heat.